2020
DOI: 10.3390/microorganisms8121948
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ecology of Streptomyces albidoflavus Strain A10 Associated with Carpenter Ant Camponotus vagus

Abstract: Antibiotics produced by symbiotic microorganisms were previously shown to be of crucial importance for ecological communities, including ants. Previous works on ant–actinobacteria symbiosis are mainly focused on farming ants, which use antifungal microbial secondary metabolites to control pathogens in their fungal gardens. In this work, we studied microorganisms associated with carpenter ant Camponotus vagus. Pronounced antifungal activity of isolated actinobacteria strain A10 was found to be facilitated by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…Ants are one of the most successful terrestrial species [ 33 ]. Many researchers devoted to screening the high biotechnological potential of ant-associated microorganisms, as well as the significant ecological impact of microbial secondary metabolites [ 5 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 34 , 35 , 36 ]. Nonetheless, most studies have mainly focused on ant–fungus–actinomycete tripartite mutualism evolved by leaf-cutting ants, which use antifungal microbial secondary metabolites produced by actinobacteria ( Streptomyces spp., Nocardia spp., Pseudonocardia spp., Amycolatopsis spp., etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ants are one of the most successful terrestrial species [ 33 ]. Many researchers devoted to screening the high biotechnological potential of ant-associated microorganisms, as well as the significant ecological impact of microbial secondary metabolites [ 5 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 34 , 35 , 36 ]. Nonetheless, most studies have mainly focused on ant–fungus–actinomycete tripartite mutualism evolved by leaf-cutting ants, which use antifungal microbial secondary metabolites produced by actinobacteria ( Streptomyces spp., Nocardia spp., Pseudonocardia spp., Amycolatopsis spp., etc.)…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that actinomycetes in insects may provide abundant resources for the development of antimicrobial agents. These symbioses are best exemplified in fungus-growing ants [ 5 , 8 , 16 ], carpenter ant [ 17 , 18 , 19 ], solitary digger wasps [ 12 ], and southern pine beetles [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the above-mentioned criteria and methodology, we identified 71 research papers from 2016 [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , ...…”
Section: Methodsunclassified
“…Well-known cytotoxic dipeptide antimycin A ( 19 ) was isolated from ant-associated Streptomyces albidoflavus A10. At low concentrations, it inhibits the growth of entomopathogenic fungi ( Conidiobolus coronatus , Beauveria bassiana and others) [ 51 ]. Ionophore antibiotics ( 84–88 ) isolated from wasp-associated Streptomyces sp.…”
Section: Data Analysis: Main Trendsmentioning
confidence: 99%
“…There is an increasing number of recent reports about the isolation of mycelial prokaryote strains from various insects [Baranova et al, 2022], and ants remain the most popular object in this respect. Indeed, it was possible to show the presence of mycelial actinobacteria capable of synthesizing broad-spectrum antibiotics in adult individuals of carpenter and harvester ants [Zakalyukina et al, 2019[Zakalyukina et al, , 2022aBaranova et al, 2020]. Thus, it can be assumed that in the insect world, "protective symbioses" are not a random phenomenon, but an established relationship.…”
Section: Introductionmentioning
confidence: 99%